CHANNELING: SEARCH OF THE METAANTHROPOLOGIC MEAS-UREMENTS OF MIND BEING IN THE UNIVERSE (based on the World Wide Web) - Tshedrin, Anatoly T. (Antropologìnì vimìri fìlosofs'kih doslìden', 2014)
The relevance of the study. In the context of religious and philosophical movements of the «New Age» gained channeling phenomenon – «laying channel», «transmission channel» information from the consciousness that is not in human form, to the individual and humanity as a whole. In the socio-cultural environment of the postmodern channeling reflects the problem of finding extraterrestrial intelligence (ETI; «ETC-problem»; SETІ problem) and to establish contacts with them, this problem has a different projection, important philosophical and anthropological measurements in culture. Investigation of mechanisms of constructing virtual superhuman personalities in the world web is not only of interest for further analysis of the problem of extraterrestrial intelligence (ETI), but also to extend subject field of anthropology of the Internet as an important area of philosophical and anthropological studies. The purpose of the study. Analysis of the phenomenon of channeling as a projection of the fundamental problems of life ETI, its representation on the World Wide Web, the impact on the archaism of postmodern culture posing problems meta an-thropological dimensions of existence in the universe of reason and contact with him in the doctrinal grounds channeling. Analysis of research on the problem and its empirical base. Clustered nature of the problem of ETI and channeling its element involves the widespread use of radio astronomy paradigm works carriers solve CETI; work in anthropology Internet; works of researchers of the phenomenon of «New Age». Empirical basis of the study are network resources, as well as texts–representatives created and introduced into circulation by the channelers, their predecessors. Research Methodology. Channeling as an object of research, its network of representation – as a matter of methods involve the use of analytical hermeneutics and archaeographic commenting text fractal logic cluster analysis. The main body. The features of channeling as cultural practices aimed at solving the problem of finding meta an-thropological dimensions of existence in the universe of the mind, as an attempt to resolve the contradiction between the theoretical ideas about extraterrestrial civilizations and the lack of empirically observable, the expected signs of their activities. The analysis of the solutions to the problems being ETI loci, its substrate base forms of activity in the Earth's socio-cultural space that offers channeling. Considered as a complete retrospective of channeling cultural practices that emerged in the western segment of the socio-cultural environment, especially its being presented in the form of postmodern religion, emphasized the role of channeling as an indicator cosmization archaism and modern culture. Scientific novelty. Channeling is one of the sociocultural system reactions on Earth absence of bilateral contacts with the ETC. Studying the mechanisms of constructing virtual superhuman personalities in the global network is one of the directions of further development of subject- thematic field of anthropology of the Internet as an important area of philosophical and anthropological studies. Conclusions. Channeling as a holistic, complex structure phenomenon connects the dynamics of transformation of humanity with establishing contacts with polymorphic ETI. Channeling is one of the sociocultural system reactions on Earth absence of bilateral contacts with the ETC. In the development of channeling manifest fractal effects associated with the reproduction of their previous ideas about the history of ETI. Retrospection channeling as cultural practices show his obedience to the law of the cultural series: a temporary phenomenon in the long-range specific chronotope culture is defined by its inclusion in the actually exist-ing set of genetically related forms. Актуальність дослідження. У контексті релігійно-філософських рухів «Нової Ери» набув поширення феномен ченнелінгу – «прокладання каналу», «передачу по каналу» інформації від свідомості, що не перебуває в людській формі, до окремої людини й людства в цілому. У соціокультурному просторі постмодерну ченнелінг відбиває проблему пошуку позаземних цивілізацій (ПЦ; «ПЦ-проблему»; проблему SETІ) і встановлення контактів з ними; ця проблема має різні проекції, важливі філолофсько-антропологічні виміри в культурі. Дослідження механізмів конструювання надлюдських віртуальних особистостей у світовій Мережі становить інтерес не тільки для подальшого аналізу проблеми позаземного розуму (ПР), але й для розширення предметного поля антропології Інтернету як важливого напрямку філолофсько-антропологічних досліджень. Ціль дослідження. Аналіз феномена ченнелінгу як проекції фундаментальної проблеми буття ПР, її репрезентації у Всесвітній павутині; вплив архаїзації культури постмодерну на постановку проблеми метаантропологических вимірів буття розуму у Всесвіту й контактів з ним у доктринальних підставах ченнелинга. Аналіз досліджень проблеми і її емпірична база. Кластерна природа проблеми неземного розуму й ченнелинга як її елемента припускає широке використання праць носіїв радіоастрономічної парадигми рішення проблеми CETІ; робіт в області антропології Інтернету; праць дослідників феномена «New Age». Емпіричною базою дослідження є мережеві ресурси, а також тексти-репрезентанти, створені й уведені в оббіг самими ченнелерами, їх попередниками. Методологія дослідження. Ченнелінг як об'єкт дослідження, його мережеві репрезентації – як предмет передбачають використання методів аналітичної герменевтики й археографічного коментування тексту, фрактальної логіки, кластерного аналізу. Виклад основного матеріалу. Розглянуто особливості ченнелінгу як культурної практики, спрямованої на вирішення проблеми пошуку метаантропологічних вимірів буття розуму у Всесвіті, як спроби вирішення протиріччя між теоретичними уявленнями про позаземні цивілізації й відсутність емпірично спостережуваних, очікуваних слідів їх діяльності. Дано аналіз варіантів вирішення проблем локусів буття ПР, його субстратної основи, форм активності в земному соціокультурному просторі, які пропонує ченнелінг. Розглянуті ретроспекції ченнелінгу як цілісної культурної практики, що сформувалася в західному сегменті соціокультурного простору; представлені особливості його буття у формі постмодерністської релігійності; підкреслена роль ченнелінгу як індикатора космізації й архаїзації сучасної культури. Наукова новизна дослідження. Ченнелінг є однією з реакцій соціокультурної системи Землі на відсутність двосторонніх контактів з ПЦ. Вивчення механізмів конструювання надлюдських віртуальних особистостей у світовій Мережі є одним з напрямків подальшого розвитку предметно-тематичного поля антропології Інтернету як важливого напрямку філолофсько-антропологічних досліджень. Висновки. Ченнелінг як цілісний, складний за структурою феномен, пов'язує динаміку трансформації людства із установленням контактів з поліморфним ПР. Ченнелінг є однією з реакцій соціокультурної системи Землі на відсутність двосторонніх контактів з ПЦ. У розвитку ченнелинга проявляються фрактальні ефекти, пов'язані з відтворенням їм попередньої історії розвитку уявлень про ПР. Ретроспекції ченнелінгу як культурної практики доводять його підпорядкованість закону культурного ряду: часова далекодія конкретного феномена в хронотопі культури визначається його включеністю в актуально існуючу сукупність генетично родинних форм.